Media literacy in the competitive intelligence process focused on social media: Interaction model applicable to organizations - Ottonicar, Selma Letícia Capinzaiki [UNESP]; Barbosa, Everaldo Henrique Dos Santos [UNESP]; Yafushi, Cristiana Aparecida Portero [UNESP]; Moraes, Cássia Regina Bassan [UNESP] (FapUNIFESP (SciELO), 2021)
The purpose of the article is to reflect the contribution of media competence to the competitive intelligence process in the context of social media. The methodology consists of a systematic review of the literature in Brazilian databases in Information Science. The discussions demonstrated relevance in the study of the theme so that organizations can reach competitiveness more easily, especially in developing countries like Brazil. The systematic review showed that the theme is little did study by Information Science, demonstrating opportunities for future research. The final considerations point to a model of interrelationship to be did use in practices of the phenomenon in organizations.
Competência midiática no processo de inteligência competitiva voltada ao uso das mídias sociais: Modelo de interrelação aplicável nas organizações
Keywords: Competitive intelligence, social media; Competitiveness; Media literacy; Systematic literature review